2015
DOI: 10.1371/journal.pone.0142413
|View full text |Cite
|
Sign up to set email alerts
|

Reward Anticipation in Ventral Striatum and Individual Sensitivity to Reward: A Pilot Study of a Child-Friendly fMRI Task

Abstract: Reward processing has been implicated in developmental disorders. However, the classic task to probe reward anticipation, the monetary incentive delay task, has an abstract coding of reward and no storyline and may therefore be less appropriate for use with developmental populations. We modified the task to create a version appropriate for use with children. We investigated whether this child-friendly version could elicit ventral striatal activation during reward anticipation in typically developing children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Bilaterally reduced FA in the uncinate has been reported following institutionalization, a severe form of global deprivation (Govindan, Behen, Helder, Makki, & Chugani, 2010). Another study reported no association between institutionalization and WM microstructure in this region (Bick, Zhu, et al, 2015), and in a community sample of adults, childhood adversitywhich included measures of both threat and deprivation-was associated with greater FA in the left uncinate fasciculus (Ugwu et al, 2015), consistent with our finding. One difference between prior work reporting decreased FA and the current investigation is that children in prior studies were adopted into well-resourced families following institutionalization in infancy and early childhood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bilaterally reduced FA in the uncinate has been reported following institutionalization, a severe form of global deprivation (Govindan, Behen, Helder, Makki, & Chugani, 2010). Another study reported no association between institutionalization and WM microstructure in this region (Bick, Zhu, et al, 2015), and in a community sample of adults, childhood adversitywhich included measures of both threat and deprivation-was associated with greater FA in the left uncinate fasciculus (Ugwu et al, 2015), consistent with our finding. One difference between prior work reporting decreased FA and the current investigation is that children in prior studies were adopted into well-resourced families following institutionalization in infancy and early childhood.…”
Section: Discussionsupporting
confidence: 91%
“…Maturation of WM microstructure is highly protracted, with ongoing development throughout childhood into late adolescence (Lebel & Beaulieu, 2011), suggesting that WM development may be particularly susceptible to postnatal environmental influences. There is rapidly emerging evidence that childhood adversity impacts the development of WM microstructure across a number of brain regions (Bick, Zhu, et al, 2015;Choi, Jeong, Polcari, Rohan, & Teicher, 2012;Ugwu, Amico, Carballedo, Fagan, & Frodl, 2015), and that adversity-related WM differences may also be related to specific types of adverse experiences (Choi et al, 2012). For example, Choi et al (2012) showed that witnessing domestic violence in childhood was associated with reduced FA in the visual limbic pathway during young adulthood.…”
mentioning
confidence: 99%
“…Reward sensitivity in children was assessed at three different levels: behavior in daily life (SPSRQ‐C reward subscale), neuropsychological task performance ( B 0 vs. 15 ), and activity in ventral striatum. Higher anticipatory activity was related to better task performance (i.e., increased response time speeding when anticipating reward), replicating our previous finding (van Hulst, de Zeeuw, Lupas, et al., ) and challenging the assumption of performance independent brain activity during an MID task (Knutson, Adams, Fong, & Hommer, ). In addition, within the combined group of children with ADHD symptoms, anticipatory ventral striatal activity was positively correlated with parent‐rated reward sensitivity.…”
Section: Discussionsupporting
confidence: 88%
“…All parents were instructed not to administer medication in the 24 hr prior to testing. All children completed a modified monetary incentive delay (MID) paradigm in the context of a functional MRI scan (van Hulst, de Zeeuw, Lupas, et al., ). After screening data quality, 27 participants were excluded on the basis of excessive head motion, three participants were excluded due to anatomical abnormalities, and two participants had to be excluded as a result of an incorrectly placed field of view (for details see Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation